Body Composition in Obese Adolescents: Deuterium Oxide Dilution Method, Bioelectrical Impedance and Predictive Equations - Maria Mendes Resende, Cristina; Simon Camelo Junior, Jose; Neves Campanelli Marcal Vieira, Marta; da Silva Castro Perdona, Gleici; Ferriolli, Eduardo; Pfrimer, Karina; Giaretta Mathias, Mariana; Pontes Monteiro, Jacqueline (Current Nutrition & Food Science, 2013)
Background & Aims: Considering that obese adolescents present alterations in the quantity of body water, fat and lean body mass, specific formulae need to be adjusted through a reference method. This study aimed to describe and compare the body composition data obtained by bioelectrical impedance analysis (BIA) and the deuterium oxide dilution method (DODM). To identify possible correlations and agreement between these two techniques and adjust linear regression models for the prediction of DODM values on the basis of BIA results. Methods: Anthropometric measurements were accomplished for obese adolescents, and their body composition was assessed by the BIA and DODM techniques. Results: Compared to the DODM technique, BIA overestimated the fat-free mass (FFM) and the total body water (TBW) and underestimated the fat mass (FM). There was a significant positive correlation but no agreement between the FFM (kg), FM (kg), and TBW (L) data achieved via DODM and BIA. The application of linear regression model adjustments to the values measured by BIA enabled prediction of the DODM values for body composition in obese adolescents. Conclusion: These formulas have been demonstrated to improve the agreement between the two methods, so a more accurate tool that is closer to the DODM reference technique has been made available for use in clinical practice.
Keywords: fat mass